The Utilization of the Wayground Application in Learning the Qur'an Surah Al-Ma'un at SD Negeri Tunggakcerme Probolinggo - Mustajib Mustajib; Endah Tri Wisudaningsih (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to describe the use of the Wayground application in learning the Qur'an Surah Al-Ma'un in grade V of SD Negeri Tunggakcerme Probolinggo. The research uses a descriptive qualitative approach. Data was collected through learning observations, interviews with school principals, Islamic Religious Education teachers, and students, as well as documentation of learning activities. The results of the study show that the use of the Wayground application is able to create more structured, interactive, and interesting learning of the Qur'an. Students' response to the use of this application was very positive, characterized by increased interest in learning, activeness, and focus of students during learning. In addition, students' understanding of the readings, meanings, and social values contained in Surah Al-Ma'un has improved. The use of the Wayground application also has a positive impact on learning effectiveness, especially in time efficiency, classroom management, and the ease of teachers in conducting evaluations. Thus, the Wayground application can be an effective digital learning medium in learning the Qur'an in elementary schools.